Trace: Translating Bankside Air Raid Shelter through Material and Spatial Tracings. Issue 1 (2nd January 2019) - Dean, Corinna; Watson, Victoria; Santo, Duarte
Abstract: This project explores spaces of tolerance by using the University of Westminster as a place for casting concrete architectural models and setting them in a dialogue with faculty members. The project's site of study was the underground air raid shelter built during World War II in the garden of the Hopton Street Almshouses in London's Bankside district. Bankside is in the Borough of Southwark, located on the southern bank of the River Thames. It runs just west of Blackfriar's Bridge to St Mary Overie Dock in the east. In recent decades, Bankside has been subject to regeneration, most notably the conversion of the former power station into the Tate Modern art gallery, which has turned Bankside into a global tourist destination. In the accelerated process of development, the underground presence of the air raid shelter has been tolerated, but has become somewhat lost.